Checklist approach to vertigo: audit of current practice in a tertiary referral center - Venkataramani, Nithya; Sachidananda, Ravi; Nagarajaiah, Rajesh Karalumangala (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Vertigo is a complex symptom which can be present in multiple conditions, some of which are life threatening. Diagnosing a patient with vertigo could sometimes be challenging and there is a need for a comprehensive, yet easily reproducible diagnostic model with emphasis on the red flag signs. A simple way to achieve this is a checklist. The aim of the study was to propose a diagnostic checklist for patients presenting with vertigo to an ENT clinic to aid diagnosis and prevent diagnostic errors. Methods: A diagnostic checklist was used in all patients who presented with the symptom of vertigo, necessary tests were conducted and referrals were done when required. Results: Out of eighty-five patients who presented with symptom of dizziness to ENT clinic, all patients received a definitive diagnosis treatment plan with the help of checklist. Conclusions: Checklist is an effective way to ensure elaborate assessment of the patient with emphasis on the red flag signs. It is a very important tool to arrive at diagnosis and formulate treatment plan.